KUALITAS DEMPUL ORGANIK DARI SERBUK KAYU JATI DAN SIRLAK - Jamal Balfas (BRIN Publishing, 2017)
Commercial wood putty products available in the market nowadays are mostly chemical solvent-based, such as epoxy and latex. These products give desirable physical, mechanical and chemical performances, however their volatile organic compounds are detrimental to the environment and harmful to the health. This paper explores the use of teak fine powder mixed with shellac and putty powder as an alternative formulation of organic wood putty. These alternative formulas were tested on tusam and rubber wood by assessing their physical, mechanical and chemical performances in comparison with the most commercial putty products, i.e. epoxy (DK1) and piroxylin (DK2). Samples of two wood species were treated by spreading them with various wood putty solutions. Weight and dimensional changes due to treatment were determined in wet and dry sample conditions. Results show that weight and dimensional gains due to spreading treatment varies according to wood species, grain orientation and putty solution. Tusam samples possessed greater weight and dimensional gains than those of rubber wood samples. All organic putty formula was able to protect wood from water intrution, but less effective than the commercial putty DK1 and DK2. The organic wood putty had lower scratch resistance and less resistant against chemical liquids than the commercial ones.